Membangun Brand Image Mahasiswa Atas Produk Shampo Pantene Melalui Pemilihan Selebrity Endorser Studi Kasus Anggun C Sasmi Sebagai Selebrity Endorser - Juliap B., Rika; Zuhdi, Saefudin; Supariyani, Emmy (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Celebrity endorser is one of marketing communication. The use of endorser is to lift more famous product’s brand. Generally use an endorser as a celebrity is to invite people to always remember the brand on their mind. So is needed a appropriate selection of celebrity endorser with the product to be brought. It is expected to affect the brand image of a product. The purpose of this study was to determine the effect of celebrity endorser selection of brand image. To find out is to find out how a good selection of celebrity endorser and appropriate so as to produce a positive brand image of a product. Research on the author is in STIE Kesatuan Bogor. By using quantitative descriptive method and causality. The result and discussion showed that Pantene celebrity endorser selectively chose the sight of the commitment of their endorser, her profession is evident in each of their carrier success. The selection process of Anggun C. Sasmi to endorse Pantene is need a quite long. This affects the Pantene’s brand image as a market leader in the position of hair science which gained several awards. Celebrity endorser selection of indicators source credibility, source attractiveness, meaning transfer, and celebrity product congruence. Source credibility of Anggun C. Sasmi was not much influence on brand image of Pantene shampoo. While a celebrity product congruence has a positive influence, dominant, significant. Value of r or the correlation coefficient between the celebrity endorser’s selection of celebrity endorsers (X) with the brand image (Y) of 0,663 means that the relation between these variables is strong. It means that if X then Y up one unit will respond by 66,3%. So, the celebrity endorser’s selection which have a right process will affect the brand image of Pantene shampoo products. Keywords: celebrity endorser, brand image, Shampoo